The Effect of Stress Management Education through Butterfly Hug on the Level of Community Knowledge: Pengaruh Edukasi Manajemen Stres melalui Butterfly Hug terhadap Tingkat Pengetahuan Masyarakat - Kurniyawan, Enggal Hadi; Adela Qiyas Aulawi; Selvia Wulandari; Dicky Endrian Kurniawan; Tri Afandi, Alfid; Rosyidi Muhammad Nur, Kholid; Agustin, Leni (Journal of Community Empowerment for Multidisciplinary (JCEMTY), 2025)
The prevalence of mental illness in Jember Regency is still relatively high, which is why health interventions to improve independence and empower the community are very important. One of the promotive efforts in the field of mental health for stress management is through the Butterfly Hug therapy. The Butterfly Hug therapy is a self-healing therapy method where it is believed that the body can heal itself naturally through positive thoughts and affirmations towards oneself. This community service activity aims to determine the impact of education related to stress management through the Butterfly Hug on the level of knowledge. Hopefully, the community's understanding of effective stress management will improve. The number of participants in the health education session was 21. The health education evaluation showed that the education implementation affected the respondents' knowledge level about stress and stress management. This indicates that health education on stress management positively impacts increasing awareness and knowledge within the community.